Implementation of Akhlakul Mahmudah Education at Madrasah Aliyah - Yuli Supriani; Nurwadjah Ahmad; Andewi Suhartini (Nazhruna: Jurnal Pendidikan Islam, 2022)
Abstract This article aims to describe and analyze the implementation of noble moral education and its supporting and inhibiting factors. The research approach is a qualitative study conducted in Madrasah Aliyah Al-Hidayah Ibun Bandung with the subject of principal and teacher research. For data collection, interviews, observations, documentation, and Focus Group Discussions were conducted. Techniques of data analysis in this research are data reduction, data display, and data verification then concluding the data that has been presented gradually to be the research findings. This paper concludes that: principals and teachers have attempted to implement noble moral education to learners through exemplary education, habituation, attention, giving advice, and educational punishment. Supporting factors of school principals who seek to disseminate school vision and mission to the school community and cooperation between school principals and other components. Inhibiting factors are still inadequate for mushola and fund allocation for religious activities.